The Principle of Confidentiality in Islamic Guidance and Counseling: A Review of Hadith (Jurusan Bimbingan dan Konseling Islam, 2022)
This paper discusses the principle of secrecy in Islamic guidance and counseling in terms of a hadith of the Prophet. The purpose of this paper is to get an explanation regarding the importance of the principle of confidentiality in Islamic guidance and counseling when viewed from the hadith of the Prophet. The method used is library research, by analyzing or reviewing writings from various sources and the most important data is the hadith of the Prophet Muhammad. From the results of the studies that have been collected and studied by researchers, it can be concluded that in carrying out general and Islamic guidance and counseling services, it is necessary to apply the principle of confidentiality so that the service can run smoothly as desired. If, in terms of the hadith of the Prophet Muhammad, the principle of secrecy is important because it is in accordance with Islamic religious teachings in which it requires a person's obligation to keep information secret from other people so that it is not known to the general public. When someone else has told us the secret, that person already believes and thinks he can protect it. As well as in the rules of the Islamic religion it has been explained that Allah has given threats to be entered into the Hellfire of Jahannam for those who violate or can be said to be unable to keep other people's secrets or disgrace.